Studies on post~ biochemical and hormonal prome of fertile and infertile oestrous cycles in Surti buffaloes - KAVANI, F S; KHASATIYA, C T; STHANKI, D J; THAKOR, D B; DHAMI, A J; PANCHAL, M T (The Indian Journal of Animal Reproduction, 2023)
A comparative study on plasma profile of biochemical, metabolic and hormonal constituents and macro-micro mineralswas studied on different days of fertile and infertile cycles (20 each) in 40 postpartum Surti buffaloes of an organised farm. Theanimals detected in oestrus after day 50 of normal calving were bred by natural service and heparinized jugular blood samples werecollected on the day of oestrus/breeding ( day 0) and subsequently on 7th, 14th and 21st day for estimation of plasma profiles ofvarious constituents. Pregnancy was confirmed per rectum 45 days post-service in non-return cases. The plasma profile revealedthat the progesterone level was significantly higher (P < 0.05) in fertile than the infertile cycle on day 14 (2.14±0.21 vs 1.20±0.19ng/ml) and day 21 (2.57±0.21 vs 0.42±0.04 ng/ml), but not at oestrus (0.37±0.02 vs 0.39±0.05 ng/ml) or day 7 (l.29±0.08 vs1.12±0.11 ng/ml) post-breeding. Moreover, the infertile buffaloes had a combined pattern of delayed rise and low level of P4indicative of insufficient luteal function. The glucose levels were apparently higher and riglycerides lower (P > 0.05) in fertile thanthe infertile cycle at most intervals, while total protein content was significantly higher (P < 0.05) on day 7 and 21, and AKP on alldays post-service in fertile than the infertile cycles, but did not vary between days/stages within the cycle. Further, the averageplasma profile of thyroid hormones (T3, T4), total cholesterol, calcium, phosphorus as well as micro-minerals, viz., Zn, Fe, Cu, Coand Mn neither varied significantly between different days nor between groups/cycles at any of the intervals post-breeding, probablydue to uniform balanced ration/nutrition and supplementation of mineral mixtures in daily ration of these animals under organizedfarm management.
Keywords: Hormone profile; metabolic profile; mineral profile; oestrous cycle; Surti buffalo